Designing Supplementary Listening Activities for Tenth-Grade Students of Senior High School - Narisa Berliana; Yohanes Gatot Sutapa Yuliana; Eka Fajar Rahmani (Journal of English Language and Education, 2026)
Listening is essential in the EFL classroom; however, the textbook lacked listening activities. This study aims to design Task-Based Language Teaching (TBLT) supplementary listening activities for tenth-grade students at SMAN 10 Pontianak. This study uses the Analysis, Design, Development model as the research and development framework. Data were collected through interviews and a questionnaire involving two English teachers, 93 tenth-grade students, and a curriculum developer. The analysis phase revealed that students and teachers require supplementary material to develop listening skills. In the design phase, the researcher developed an e-book containing nine TBLT-based listening activities, each structured into pre-task, main task, and post-task phases, supported by twelve audio files accessible via QR codes. In the development phase, an internal evaluation was conducted, and the product achieved a high score and was categorized as very feasible across quality criteria, including curriculum alignment, TBLT implementation, and usability.